THE POSITION OF THE ARBITRATION COMPROMISE DEED IN TERMS OF THE OBLIGATION OF THE SIGNATURES OF THE PARTIES IN THE MAKING OF THE DEED BY A NOTARY - SYIFA DITA NOVEILLA (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
Article 9 paragraph (2) of Law Number 30 of 1999 concerning on Arbitration and Alternative Dispute Resolution stating a compromise deed must be made by a notary once the parties cannot sign the deed. Meanwhile, when undertaking his position, Notaries are provided with Law Number 2 of 2014 jo. Law Number 30 of 2004 concerning the Position of a Notary regarding the notary's obligation to declare the deed in front of the audience along with witnesses and to be signed by parties including the person, the witness, and the Notary. This research used a normative juridical method with a statutory approach originating from secondary data. The result shows that a compromise deed that cannot be signed by the parties included in the form of a relaas deed, furthermore, despite being not signed by the parties, this deed remains evidentiary powerful of a deed signed by the parties.Keywords: Deed of Compromise; Arbitration; Signature Obligation; Notary.